2014
DOI: 10.3390/ijms151223658
|View full text |Cite
|
Sign up to set email alerts
|

Refolded scFv Antibody Fragment against Myoglobin Shows Rapid Reaction Kinetics

Abstract: Myoglobin is one of the early biomarkers for acute myocardial infarction. Recently, we have screened an antibody with unique rapid reaction kinetics toward human myoglobin antigen. Antibodies with rapid reaction kinetics are thought to be an early IgG form produced during early stage of in vivo immunization. We produced a recombinant scFv fragment for the premature antibody from Escherichia coli using refolding technology. The scFv gene was constructed by connection of the VH–VL sequence with a (Gly4Ser)3 link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…The far‐UV CD spectra (190–240 nm) for the six scFvs (Fig. d) showed the scFvs were predominantly β‐sheets, as expected for typical members of the immunoglobulin family, including scFvs (Supplementary Table SVI) (Blanco‐Toribio et al, ; Glaven et al, ; Gregoire et al, ; Lee et al, ; Song et al, ). The scFv‐2D10 (PDB ID‐ 4H0H) crystal structure showed the presence of 4% helical and 47% beta sheet secondary structures (Tapryal et al, ), whereas the CD data for the scFv‐2D10 in our hands retrieved 3.4, 5, and 9% helical and 40, 38, and 27% beta sheet structures from CDSSTR, CONTIN, and GOR4, respectively (Supplementary Table SVI).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The far‐UV CD spectra (190–240 nm) for the six scFvs (Fig. d) showed the scFvs were predominantly β‐sheets, as expected for typical members of the immunoglobulin family, including scFvs (Supplementary Table SVI) (Blanco‐Toribio et al, ; Glaven et al, ; Gregoire et al, ; Lee et al, ; Song et al, ). The scFv‐2D10 (PDB ID‐ 4H0H) crystal structure showed the presence of 4% helical and 47% beta sheet secondary structures (Tapryal et al, ), whereas the CD data for the scFv‐2D10 in our hands retrieved 3.4, 5, and 9% helical and 40, 38, and 27% beta sheet structures from CDSSTR, CONTIN, and GOR4, respectively (Supplementary Table SVI).…”
Section: Resultssupporting
confidence: 59%
“…To confirm correct folding of scFvs, the secondary structures of the six purified scFvs were monitored by far‐UV CD spectroscopy and compared to that of other scFvs (Blanco‐Toribio et al, ; Glaven et al, ; Song et al, ). The far‐UV CD spectra (190–240 nm) for the six scFvs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main drawbacks of E . coli as a host organism for protein expression and purification is due to protein expression in the insoluble fraction, as is the case for most scFvs in the literature [ 25 , 40 43 ] and also for scFv-h3D6-Ec. In this case, the insoluble fraction needs to be chemically solubilized and proteins, which are denatured, must be refolded.…”
Section: Resultsmentioning
confidence: 99%
“…The production of scFvs in soluble and active form in E . coli is difficult to obtain, since the reducing environment of the bacterial cytoplasm is not compatible with disulfide bonds formation, resulting in unstable molecules or even aggregates [ 47 ], moreover several studies have reported the same issue with antibody fragments cloned into pET28a vector [ 45 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%